2020
DOI: 10.26434/chemrxiv.13274543.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Situ Generation of Radical Initiators: Air Stable Amine-Borane Complexes Promote Atom Transfer Radical Additions of Alkyl Halides to Alkenes

Abstract: Despite their instability, carbon-centered radicals have been involved as intermediates in many organic transformations that are essential to mankind. Radical polymerization,1-5 for example, provides a large part of polyacrylates and polystyrenes used as commodities in our everyday life. On a molecular level, the outcome of radical-mediated reactions is usually very different from those obtained via classical ionic based organic reactions. This is known since the 1930’s6 and has witnessed extensive development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Amine-borane complexes have been extensively used in the literature as hydrogen reservoirs [40], as reducing agents in various transformations, including the reduction of aldehydes, amides and ketones, reductive aminations, alkene hydroboration, and carbon bond forming reaction [41,42], as well as various boronate and borinic acid precursors [43][44][45][46][47]. More recently, it has been shown that some of these common amine-borane complexes can also be used as radical initiators for atom transfer radical addition of alkyl halides to alkenes [48]. They were also used in the free-radical polymerization of alkene-containing monomers such as methyl methacrylate or styrene [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amine-borane complexes have been extensively used in the literature as hydrogen reservoirs [40], as reducing agents in various transformations, including the reduction of aldehydes, amides and ketones, reductive aminations, alkene hydroboration, and carbon bond forming reaction [41,42], as well as various boronate and borinic acid precursors [43][44][45][46][47]. More recently, it has been shown that some of these common amine-borane complexes can also be used as radical initiators for atom transfer radical addition of alkyl halides to alkenes [48]. They were also used in the free-radical polymerization of alkene-containing monomers such as methyl methacrylate or styrene [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Scheme 2, we envisioned that the amine-borane complex-initiated reaction of SF 5 Cl with alkenes would proceed following a mechanism similar to the amine-borane complexinitiated carbohalogenation of alkenes [48]. The first step would involve the formation of a trialkylborane species via the hydroboration of the alkene, as previously observed by 11 B NMR spectroscopy [48,49]. In the presence of oxygen, the trialkylborane would, similarly to Et 3 B, generate an alkyl radical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation